EMOTIONAL INTELLIGENCE AS A COMPONENT OF DISTANCE EDUCATION - Polukhina , Maryna; Anpilohova , Tetiana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article presents an analysis of emotional intelligence as an independent psychological characteristic of a person and its influence on human cognitive processes. It has been proven that student learning outcomes can be improved by adding an emotional component to the educational platform. The pedagogical approach to the organization of the distance learning process using the Flippity website is revealed, taking into account emotions as an important and integral component of the intellectual development of the individual.